Kunxian Capsule for Rheumatoid Arthritis: Inhibition of Inflammatory Network and Reducing Adverse Reactions Through Drug Matching - Tang, Yujun; Zhang, Yi; Li, Lin; Xie, Zhijun; Wen, Chengping; Huang, Lin (Frontiers in Pharmacology, 2020)
Tripterygium wilfordii Hook.f and Tripterygium hypoglaucum (H.Lév.) Hutch is effective herbs to prevent aggravation of Rheumatoid arthritis (RA). However, both of them show severe side effects in the reproductive system and other systems. Kunxian Capsule (KX), a Traditional Chinese Medicine (TCM) patent prescription, comprised of 4 herbs, including H.Lév. Hutch, is reported to be an available prescription in treating RA with fewer side effects as compares to Tripterygium tablets. To reveal the pharmacological mechanism of KX in RA treatment and side effect alleviation, we collected related information of KX from open-access databases and performed various analyses. 1354 targets were identified in KX. These targets were enriched in the calcium signaling pathway, cAMP signaling pathway, cGMP-PKG signaling pathway and PI3K-AKT signaling pathway, forming biological functions, such as cofactor binding, coenzyme binding, etc. These pathways or functions mostly affect cell cycle, differentiation, and maturation of Th17 cells, macrophage, and synovial fibroblast. These targets also act on the IL-17 signaling pathway, Th17 cell differentiation signaling pathway and TNF signaling pathway, which is related to inflammation response inhibition. Next, a disease network was constructed, which indicated IMPDH2, MTHFD1 are the key genes answering for the side effects of H.Lév. Hutch. The side effect–related genes lead to the negative regulation of nucleic acid, which could be restored by the rest 3 herbs through some positive amino acid metabolism. In conclusion, KX is a relatively safe alternative approach in RA intervention.